Comparison of two PCR-based human papillomavirus genotyping methods - Castle, Philip E. (2008)
We compared two consensus primer PCR human papillomavirus (HPV) genotyping methods for the detection of individual HPV genotypes and carcinogenic HPV genotypes as a group, using a stratified sample of enrollment cervical specimens from sexually active women participating in the NCI/Costa Rica HPV16/18 Vaccine Efficacy Trial. For the SPF10 method, DNA was extracted from 0.1% of the cervical specimen by using a MagNA Pure LC instrument, a 65-bp region of the HPV L1 gene was targeted for PCR amplification by using SPF10 primers, and 25 genotypes were detected by reverse-line blot hybridization of the amplicons. For the Linear Array (LA) method, DNA was extracted from 0.5% of the cervical specimen by using an MDx robot, a 450-bp region of the HPV L1 gene was targeted for PCR amplification by using PGMY09/11 L1 primers, and 37 genotypes were detected by reverse-line blot hybridization of the amplicons. Specimens (n 1,427) for testing by the LA method were randomly selected from strata defined on the basis of enrollment test results from the SPF10 method, cytology, and Hybrid Capture 2. LA results were extrapolated to the trial cohort (n 5,659). The LA and SPF10 methods detected 21 genotypes in common; HPV16, -18, -31, -33, -35, -39, -45, -51, -52, -56, -58, -59, -66, -68, and -73 were considered the carcinogenic HPV genotypes. There was no difference in the overall results for grouped detection of carcinogenic HPV by the SPF10 and LA methods (35.3% versus 35.9%, respectively; P 0.5), with a 91.8% overall agreement and a kappa value of 0.82. In comparisons of individual HPV genotypes, the LA method detected significantly more HPV16, HPV18, HPV39, HPV58, HPV59, HPV66, and HPV68/73 and less HPV31 and HPV52 than the SPF10 method; inclusion of genotype-specific testing for HPV16 and HPV18 for those specimens testing positive for HPV by the SPF10 method but for which no individual HPV genotype was detected abrogated any differences between the LA and SPF10 methods. The LA method detected more carcinogenic-HPV-genotype infections per specimen than the SPF10 method (P < 0.001). In conclusion, the LA method and the SPF10 method with HPV16 and HPV18 genotype-specific detection among ungenotyped HPV-positive specimens were comparable for detection of HPV16 and HPV18, the two HPV genotypes targeted by current prophylactic HPV vaccines. Both approaches are suitable for monitoring the impact of HPV16/18 vaccines in clinical trials.